Liberalisasi Fee Advokat: Antara Perlindungan Dan Kompetisi Terhadap Advokat Indonesia - Delarosa, Stella (Veritas et Justitia, 2016)
Abstract  This article analyses issues related to the implementation of fee liberalization by the ASEAN Economic Community (AEC) and its effect to the legal service business sector. Indonesian lawyers, as a consequence, will then have to compete with foreign legal service providers. It is assumed that through fair and transparent competition a more accountable business atmosphere can be created. However, a number of legal regulations at the national level establishes non-trade barriers, effectively obstructing the AEC’ market liberalization project. The authors standing here is that the policy of protecting domestic lawyers or advocates should be rescinded and to that purpose Indonesia should amend the prevailing Law on Advocate.